Promiscuous elites and economic development - Elise S. Brezis (Bar-Ilan University, Department of Economics, 2012)
This paper analyzes the interconnection between elites and its effects on economic growth. For decades, the bureaucratic elite has been joining the business elite after leaving office, and this in growing numbers. This relationship has been termed the revolving door in English, pantouflage in French, and amakudari [descent from heaven] in Japanese. The purpose of this paper is to explain why this social behavior takes place, and why the political elite does not try to prevent it. Moreover, this paper shows that the bureaucratic elite obtains excessive bureaucratic power, and that promiscuous elites actually lead to lower economic growth.
Keywords: H10; H70; O11; O43; 330; elites; bureaucracy; abuse of power; revolving door; economic growth; Elite; Bürokratie; Arbeitsmobilität; Privatwirtschaft; Macht; Soziales Verhalten; Wirtschaftswachstum; Institutionalismus; Theorie